Educational Costs of Residents in a Teaching Hospital: a case study - Mahmoud Reza Aleboyeh; Aziz Reza pour; Zahra Meshkani; Vahid Alipour; Maryam Soleimani movahed (Kerman University of Medical Sciences, 2019)
Educational Costs of Residents in a Teaching Hospital: a case study   Aleboyeh Mahmoud Reza1, Reza pour Aziz2, Meshkani Zahra3*, Alipour Vahid4,  Soleimani movahed Maryam4   1. Associate Professor, Department of Anesthesiology, Faculty of Medicine, Iran University of Medical Sciences, Tehran, Iran 2. Associate Professor, Health Management and Economics Research Center, Iran University of Medical Sciences, Tehran, Iran 3. Ph.D. Student in Health Economics, Health Management and Economics Research Center, Iran University of Medical Sciences, Tehran, Iran 4. Assistant Professor, Health Management and Economics Research Center, Iran University of Medical Sciences, Tehran, Iran Correspondence: School of Public Health, Campus of Bam, Khalij Fars Highway, Bam University of Medical Sciences. Tel: 009888671614                                                  Email: Z_moshkani@yahoo.com Abstract: Background & Objectives: Residents spend much of their time at the hospitals to earn their required educational skills and although they act as a kind of human resource in the hospital, they increase hospital costs. The present study was designed to calculate the share of educational costs of different medical residents in hospitals. Methods: In this descriptive and applied study performed in one of the hospitals affiliated to Iran University of Medical Sciences, the hospital cost items of education of residents in different medical fields during the academic year of 2017-2018 were identified by use of two scenarios. Results: In short, mean educational cost of one resident in the studied academic year was about 5357$ based on the first scenario and about 5404 $ according to the second scenario. Based on both scenarios, salaries paid to residents accounted for more than 50% of the costs followed by the cost of consumed materials by residents. Forensic Medicine and Anesthesiology residency programs had respectively the lowest and highest share of costs in both scenarios.   Conclusion: The cost of training in the hospital is different among residency fields based on the required tests and errors in each field. But, in order to save hospital costs, the culture of optimal use of materials as well as medical equipment should be taught to residents.   Keywords: Education Economics, Costing, Direct Costs, Residents, Teaching hospital   Citation: Aleboyeh MR, Reza pour A, Meshkani Z, Alipour V, Soleimani movahed M. Educational Costs of Residents in a Teaching Hospital: a case study. Journal of Health Based Research 2019; 5(2): 117-30.